HbpR, a New Member of the XylR/DmpR Subclass within the NtrC Family of Bacterial Transcriptional Activators, Regulates Expression of 2-Hydroxybiphenyl Metabolism in Pseudomonas azelaica HBP1 - Jaspers, Marco C. M. (American Society for Microbiology, 2000)
The regulation of 2-hydroxybiphenyl and 2,2′-dihydroxybiphenyl degradation in Pseudomonas azelaica is mediated by the regulatory gene, hbpR. The hbpR gene encodes a 63-kDa protein belonging to the NtrC family of prokaryotic transcriptional activators and having the highest homology to members of the XylR/DmpR subclass. Disruption of the hbpR gene in P. azelaica and complementation in trans showed that the HbpR protein was the key regulator for 2-hydroxybiphenyl metabolism. Induction experiments with P. azelaica and Escherichia coli containing luxAB-based transcriptional fusions revealed that HbpR activates transcription from a promoter (P(hbpC)) in front of the first gene for 2-hydroxybiphenyl degradation, hbpC, and that 2-hydroxybiphenyl itself is the direct effector for HbpR-mediated activation. Of several compounds tested, only the pathway substrates 2-hydroxybiphenyl and 2,2′-dihydroxybiphenyl and structural analogs like 2-aminobiphenyl and 2-hydroxybiphenylmethane were effectors for HbpR activation. HbpR is therefore, to our knowledge, the first regulator of the XylR/DmpR class that recognizes biaromatic but not monoaromatic structures. Analysis of a spontaneously occurring mutant, P. azelaica HBP1 Prp, which can grow with the non-wild-type effector 2-propylphenol, revealed a single mutation in the hbpR gene (T613C) leading to a Trp→Arg substitution at amino acid residue 205. P. azelaica HBP1 derivative strains without a functional hbpR gene constitutively expressed the genes for 2-hydroxybiphenyl degradation when complemented in trans with the hbpR-T613C gene. This suggests the importance of this residue, which is conserved among all members of the XylR/DmpR subclass, for interdomain repression.